Immediate Implant Placement by Interradicular Bone Drilling before Molar Extraction: Clinical Case Report with One-Year Follow-Up - Stuardo Valenzuela; José M. Olivares; Nicolás Weiss; Dafna Benadof (Hindawi Limited, 2018)
The placement of immediate implants in the posterior sector is a widespread procedure where the success and survival rates are similar to those of traditional protocols. It has several anatomical challenges, such as the presence of interradicular bone septa that hinder a correct three-dimensional positioning of the implant and may compromise primary stability and/or cause damage of neighboring structures. The aim of this article is to present the treatment and the one-year clinical follow-up of a patient who received immediate implant placement using an interradicular bone-drilling technique before the molar extraction.